Efektivitas Konseling Kelompok Kognitif Perilaku dengan Teknik Aktivasi Perilaku untuk Meningkatkan Motivasi Belajar Siswa SMP - Pristiwanti, Yuwanita; Indreswari, Henny; Ramli, M. (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study aims to test the effectiveness of group counseling with a Cognitive Behavioral (CBT) approach using behavioral activation techniques in improving learning motivation of Junior High School (SMP) students. The research design used was a pretest–posttest one group design with seven eighth grade students who had low learning motivation scores as participants. The intervention was carried out in four group counseling sessions that focused on behavioral activation, such as arranging meaningful activities, scheduling learning, and recording and self-reflection. The results of the analysis showed an increase in the average learning motivation score from 75.4 to 114.8 with a significance value of p = 0.005, which means that the change was statistically significant. These findings indicate that behavioral activation techniques in CBT group counseling are effective in encouraging changes in student learning behavior from passive to productive. This study provides an empirical contribution to the practice of school guidance and counseling services, as well as enriching evidence-based intervention approaches in improving learning motivation of junior high school students.